GAYA KEPEMIMPINAN KEPALA DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DI DESA TALUMAE KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Arifin, Muh. Indra; Lukman; Sellang, Kamaruddin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Infrastructure development is an important aspect in supporting the development of a region. There is development in an area. Leadership style is a person's way of influencing other people, the role of a leader also influences the success of infrastructure development. This research is to find out and analyze the leadership style of village heads regarding infrastructure development. This research uses quantitative research with a descriptive approach. The data analysis method in this research is by means of validity testing, reliability testing, and basic linear regression analysis used in the data analysis procedure using the SPSS version 21 program, and data collection is by using methods, interviews, documentation, literature review and observation, research location. in Talumae Village, Watang Sidenreng District, Sidenreng Rappang Regency. The aim to be achieved in this research is to analyze the factors inhibiting infrastructure development. The population of this research is the number of Family Cards (KK) of 633 people selected using nonprobality sampling methodology and the Slovin formula as a sampling method. The results of the research show that with an average score of 68% in the good category, the village head's leadership style is in the good category, infrastructure development has an average score of 62.2% with a calculated t value of 2,556 ≥1,665 with a percentage of influence amounting to 42.39% based on the results of SPSS data processing using simple linear regression, Ha was accepted and Ho was rejected.